Histological Ex Vivo Evaluation of the Suitability of a 976 nm Diode Laser in Oral Soft Tissue Biopsies - Gaspare Palaia; Federico Renzi; Daniele Pergolini; Alessandro Del Vecchio; Paolo Visca; Gianluca Tenore; Umberto Romeo (International Journal of Dentistry)
Introduction. Laser-induced thermal effects can preclude a safe histological evaluation of biopsy resection margins. The aim of this study was to evaluate the suitability of a 976 nm diode laser in oral soft tissue biopsies in an ex vivo study. Materials and Methods. A 976 nm diode laser (Solase®, Lazon Medical Laser, China) has been used in the contact mode, using a 400 μm fiber tip, at different parameters from 4 to 6 W in the continuous wave (CW), with a fluence between 3184 and 4777 J/cm2, and pulsed wave (PW) mode, with a fluence between 318,4 and 477,7 J/cm2, to obtain 30 samples from fresh pig cadaver tongues. All specimens were subdivided into 6 groups (from A to F), and each group consisted of 5 samples. Two sections were obtained from each sample. A histological analysis was performed using an optical microscope at magnifications of 5x and 10x. Statistical analysis was carried out using Kruskal–Wallis and Dunn’s tests. Results. The results showed that histological readability was optimal in all the samples. The thermal damage was negligible in all groups. The average thermal damage was 208.40 ± 133.81 μm in the epithelial tissue and 330.14 ± 147.45 μm in the connective tissue. The statistical analysis showed no differences between the groups (p > 0.05). Conclusion. A 976 nm diode laser demonstrated good surgical effectiveness that provoked little peripheral damage in the cut edges and allowed a safe histological diagnosis. Clinical Relevance. In oral pathology, many times, there is fear in using the laser to remove some lesions due to its thermal effect on the tissues close to the lesion. This effect is always present in the use of the laser, but the intent is to minimize this effect to have as little alteration as possible on the surrounding tissues.